The Meanings of Coming out Constructed by Homosexual Males in Pivate and Public Spheres of their Experiences - Lucyna Kopciewicz; Marcin Welenc (University of Lower Silesia, 2013)
This article is concerned with results of phenomenographic study in which the meanings of coming out constructed by homosexual males are identified. Authors discuss the issue of otherness as a category that describes the self-experience of gays as well as the problem of their constructed sexual identity as unstable and changeable. An important part of the article is the problem of pedagogical tools and strategies used by family members when confronting the homosexual identity.